Guiding principles on business and human rights - United Nations (United Nations, 2011)
The Guiding Principles were developed by the former Special Representative of the SG on the issue of human rights, transnational corporations and other business enterprises. They have been widely endorsed by international and regional organizations, States, business enterprises, industry and trade union networks, and civil society organizations. They reflect and build on the three-pillar structure of the “Protect, Respect and Remedy” framework, comprising of 31 principles, each followed by a brief commentary. Together, the Guiding Principles outline steps for States to ensure and foster business respect for human rights; provide a blueprint for companies to respect human rights; and offer a set of benchmarks for stakeholders to assess business respect for human rights.